Two Decades of Change: Russian-Georgian Relations after Rose Revolution (2003–2023) - A. K. Dudayti (Научный диалог)
This article analyzes the transformations in Russian-Georgian relations following the Rose Revolution. The study aims to evaluate the key phases and significant aspects of the bilateral relationship that have notably influenced regional political dynamics. Utilizing a comprehensive approach, the research draws on official documents, media publications, and analytical reports. It employs methods of political analysis, historical review, and comparative analysis, facilitating a thorough understanding of the issues at hand. The findings demonstrate that the revolution resulted in a deterioration of relations, particularly following the imposition of visa and trade restrictions. In subsequent years, the relationship exhibited fluctuations with periods of escalation. Notably, recent years have seen a reduction in tensions and a resumption of dialogue. The study identifies critical factors affecting the dynamics of relations, including Georgia's foreign policy orientations and regional conflicts. It emphasizes that political will and international mediation play a crucial role in the process of rebuilding trust between the two nations, presenting new challenges and opportunities for resolving their differences.